Come+ON! 50 Years of the Club of Roma: Reflections and critisism. - Yanitsky, Oleg N. (Advances in Social Sciences Research Journal, 2018)
The article presents the reflections and some critical remarks on the Report prepared for the Club of Rome’s 50th Anniversary in 2018 (Von Weizsäcker and Wijkman, 2018). The Report is significant for many reasons; it shows the importance of long-term research project of a global scale; it confirms that such study has to be multidisciplinary one; it shows that any attempt to modernize capitalism in its recent form is useless; it points to the dangers of overpopulation of the planet and endless consumerism; Report demonstrates the importance of close interdependence between the planet evolution and reflections on it by the community of scientists and scholars; it is sees our planet as diversified but an integrated wholeness; and it is a great merit of this project that being initially initiated by scientists from the global North, it gradually involved in its orbit the scientists and scholars from the global South. At the same time the Report 2018, to my mind, has some weak points. First, the Report has no all-embracing global model of the planet evolution. It means that there is no separate man and nature but there is a sociobiotechnical system (hereafter, the global SBT-system), and this wholeness is maintained by permanently switching system of networks. Second, this SBT-system is constructed under conditions of the Fourth technological revolution. Third, a sustainability of any system is maintained by its permanent development, it’s a law of nature and society. Fourth, the interactions between a system’s parts are not limited by exchange of information or resources, these interactions have a metabolic character. Fifth, the Report’s authors speak only about the limits of growth but no word concerning all-embracing and all-penetrating risks. Sixth, the overpopulation is a danger but the phenomenon of the ‘strength of the weakness’ is much more serious. Seventh, today the club form for developing global ideas is insufficient. Global scientific community is needed in in a permanent global research project backed by a movement of scientists and scholars aimed at reducing international tension and threat of global risks.